2020
DOI: 10.1098/rsos.191356
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 9,10-phenanthrenequione on antioxidant indices and metabolite profiles in Takifugu obscurus plasma

Abstract: Derived from polycyclic aromatic hydrocarbons (PAHs), oxygenated-PAHs (oxy-PAHs) may pose hazards to aquatic organisms, which remain largely unknown. Takifugu obscurus is an important anadromous fish species of high economic and ecological values. In the present study, T. obscurus was acutely exposed to 44.29 µg l −1 9,10-phenanthrenequione (9,10-PQ) for 96 h. Changes of antioxidant indices and metabolite profiles in plasma were compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…171 After acute exposure to 9,10-phenanthrenequinone in T. obscurus, four metabolic pathways are affected, and the 9,10phenanthrenequinone induced oxidative stress and causes neurotoxicity in fish. 172 Previous studies have suggested that the ingestion of PAHs and the derivatives could cause neurotoxicity. After maternal perinatal dietary intake of PAHs, adult male rats showed increased anxiety-related behaviors and decreased metabolism in several different brain regions.…”
Section: Other Toxicitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…171 After acute exposure to 9,10-phenanthrenequinone in T. obscurus, four metabolic pathways are affected, and the 9,10phenanthrenequinone induced oxidative stress and causes neurotoxicity in fish. 172 Previous studies have suggested that the ingestion of PAHs and the derivatives could cause neurotoxicity. After maternal perinatal dietary intake of PAHs, adult male rats showed increased anxiety-related behaviors and decreased metabolism in several different brain regions.…”
Section: Other Toxicitiesmentioning
confidence: 99%
“…Studies have reported that in differentiated human neuroblastoma SKN-SH cell lines, both parent PAHs and APAHs including dibenzothiophene and retene produce neurotoxicity in a concentration-dependent manner, and APAHs are more toxic than parent PAHs . After acute exposure to 9,10- phenanthrenequinone in T. obscurus , four metabolic pathways are affected, and the 9,10-phenanthrenequinone induced oxidative stress and causes neurotoxicity in fish …”
Section: The Health Impact Of Pah Derivatives On Humans and Animalsmentioning
confidence: 99%